Improving the performance of transglutaminase-crosslinked microparticles for enteric delivery. (October 2016) - Tello, Fernando; Prata, Ana S.; Rodrigues, Rodney A.F.; Sartoratto, Adilson; Grosso, Carlos R.F.
Abstract: Various agents for cross-linking have been investigated for stabilizing and controlling the barrier properties of microparticles for enteric applications. Transglutaminase, in addition to being commercially available for human consumption, presents inferior cross-linking action compared to glutaraldehyde. In this study, the intensity of this enzymatic cross-linking was investigated in microparticles obtained by complex coacervation between gelatin and gum Arabic. The effectiveness of cross-linking in these microparticles was evaluated based on swelling, release of a model substance (parika oleoresin: colored and hydrophobic) and gastrointestinal assays. The cross-linked microparticles remained intact under gastric conditions, whereas the uncross-linked microparticles have been dissolved. However, all of the microparticles have been dissolved under intestinal conditions. The amount of oily core that was released decreased as the amount of transglutaminase increased. For the most efficient microparticles (50 U/g of protein), the performance was improved by increasing the pH of cross-linking from 4.0 to 6.0, resulting in a release of 17.1% rather than 32.3% of the core material. These results were considerably closer to the 10.3% of core material released by glutaraldehyde-cross-linked microparticles (1 mM/g of protein). Graphical abstract: Highlights: Microparticles were obtained by complex coacervation between gelatin and gum Arabic. Microparticles were cross-linked with transglutaminase or glutaraldehyde at pH 4.0 and 6.0. Microparticles maintained their integrity in gastric conditions and solubilized at intestinal conditions. Microparticles cross-linked at pH 6.0 were more efficient compared to those cross-linked at pH 4.0. The release behavior of TG-crosslinked microparticles was considerably closer to that of the GLU-crosslinked microparticles.